Effekter av IRB-metoden på bankenes utlån til norske foretak; Effects of the IRB approach on bank lending to Norwegian enterprises - Henrik Andersen; Ragnar Enger Juelsrud; Andreas Ravndal Kostøl (Norges Bank, 2020)
– This paper analyses how the introduction of the IRB approach may have affected banks' lending to enterprises, lending margins and portfolio quality in Norway. Our results show that the IRB banks' lending margins decreased compared with the standardised approach banks following the introduction of the IRB approach. Growth in lending to the corporate market was also higher for the IRB banks than for the standardised approach banks during the first years after the introduction. However, this may be the result of factors other than the IRB approach. Our analyses do not indicate that the IRB approach has led to finer granularity in the pricing of corporate loans. We find some support for the hypothesis that the IRB approach may have improved the quality of banks' portfolios.
hdl:11250/2655712
Keywords: 330; regulation; banks; IRB; enterprises; credit